Decentralization and territorial politics: the dilemma of constructing and managing identities in Uganda - Nsamba, Morris Adam (Informa UK Limited, 2013)
By examining the process of internal boundary adjustment in the Karamoja region of Uganda, this paper argues that internal boundary adjustments in Uganda have been pursued along ethnic lines, leading to a territorial kind of citizenship and an ethnic ‘containerization’ of communities. Based on an examination of the 2001 and 2011 presidential elections in Uganda's Acholi and Lango regions, the paper further argues that internal administrative boundary adjustments in Uganda have a political usage and meaning that goes beyond the official rhetoric of administrative efficiency used to justify these reforms. Internal boundary adjustment does not, however, always lead to the political ends intended by the ruling party. Both the National Resistance Army/Movement (NRA/M) government and opposition parties have attempted, and benefitted from, internal boundary adjustments. The empirical data presented are based on official reports and documents from the Government of Uganda, Electoral Commission election reports, and a review of published books, journals and newspapers articles.